Comparison of buccal midazolam and rectal diazepam for seizures in children. (2nd March 2023) - McKie, Katrina; Raby, Peter
Abstract : Background: buccal midazolam and rectal diazepam are used as first-line drugs to control seizures in children. Immediate treatment and management of a continuing seizure is vital to ensure its safe, effective and prompt termination. Aim: To allow practitioners to evaluate the safety and efficacy of buccal midazolam versus rectal diazepam when treating seizures in children. Methods: A systematic review process was used to identify sources from CINAHL, MEDLINE, Embase, Google Scholar and the Cochrane Library, published in English between February 1999 and June 2010 Findings: five studies, totalling 676 patients, received buccal midazolam or rectal diazepam for seizures were identified. Treatment response occurred within 293 (76%) of 386 episodes treated with buccal midazolam and 248 (65%) of 383 episodes where rectal diazepam was used. There was no significant difference between groups regarding incidence of respiratory depression. Conclusion: the reviewed articles suggest that buccal midazolam is as effective as rectal diazepam for the termination of seizures.